Designed Microdevices for In Vitro Diagnostics. Issue 10 (15th September 2017) - Sun, Xuming; Wan, Jing jing; Qian, Kun
Abstract: In vitro diagnostics (IVD) refers to in vitro tests of biological specimens and contributes to two‐thirds of clinical diagnosis. There are two major components to consider for the construction of devices for IVD, including: i) capture and recognition; and ii) detection methods. Herein, the principle, design, and application of microdevices regarding these two routes in recent progress for IVD are shown. Microarrays, microfluidics, and nanodevices are reviewed for capture and recognition. Mass spectrometry, fluorescence, electrochemistry, and so on are summarized as detection methods. The roles of materials in devices toward diverse applications are elucidated with the aims of designing materials for high‐performance device toward precision medicine and initiating the development of advanced diagnostic tools involving various biomarkers. Abstract : In vitro diagnostics (IVD) relies on materials‐based devices. The principle, design, and application of microdevices for IVD are highlighted. Two major components of microdevices are elucidated: i) capture and recognition; and ii) detection methods. A brief handbook is provided, to aid in the exploration, and extend efficient devices for diagnostic application.